2003
DOI: 10.1523/jneurosci.23-17-06703.2003
|View full text |Cite
|
Sign up to set email alerts
|

Impaired NMDA Receptor-Mediated Postsynaptic Function and Blunted NMDA Receptor-Dependent Persistent Pain in Mice Lacking Postsynaptic Density-93 Protein

Abstract: Modification of synaptic NMDA receptor (NMDAR) expression influences NMDAR-mediated synaptic function and associated persistent pain. NMDARs directly bind to a family of membrane-associated guanylate kinases (MAGUKs) that regulate surface and synaptic NMDAR trafficking in the CNS. We report here that postsynaptic density-93 protein (PSD-93), a postsynaptic neuronal MAGUK, is expressed abundantly in spinal dorsal horn and forebrain, where it colocalizes and interacts with NMDAR subunits NR2A and NR2B. Targeted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
147
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(161 citation statements)
references
References 66 publications
13
147
1
Order By: Relevance
“…Aside from promoting cell surface channel clustering, we find that the association between Kir2.1 and PSD-93␦ profoundly suppresses the rate of Kir2.1 internalization, effectively stabilizing the channel in the membrane. A role for MAGUKs in the regulation of channel and receptor surface expression is supported by the finding that deletion of the C-terminal PDZ binding motif of NR2B subunits increases the rate of NMDAR internalization in neurons (34), and by a recent study that shows a reduction of surface NR2A and NR2B expression in spinal dorsal horn neurons of PSD-93 knockout mice (39). The rate of internalization of Kv1.4 and Kv4.2 channels is also reduced when coexpressed with PSD-95 (33,43), and at least in the case of Kv1.4, surface stabilization seems to intimately linked with channel clustering, since PSD-95 mutants that bind but do not cluster Kv1.4 allow rapid channel endocytosis (33).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Aside from promoting cell surface channel clustering, we find that the association between Kir2.1 and PSD-93␦ profoundly suppresses the rate of Kir2.1 internalization, effectively stabilizing the channel in the membrane. A role for MAGUKs in the regulation of channel and receptor surface expression is supported by the finding that deletion of the C-terminal PDZ binding motif of NR2B subunits increases the rate of NMDAR internalization in neurons (34), and by a recent study that shows a reduction of surface NR2A and NR2B expression in spinal dorsal horn neurons of PSD-93 knockout mice (39). The rate of internalization of Kv1.4 and Kv4.2 channels is also reduced when coexpressed with PSD-95 (33,43), and at least in the case of Kv1.4, surface stabilization seems to intimately linked with channel clustering, since PSD-95 mutants that bind but do not cluster Kv1.4 allow rapid channel endocytosis (33).…”
Section: Discussionmentioning
confidence: 95%
“…Abundant PSD-93 expression of unknown isoforms has been reported previously in the superficial dorsal horn of spinal cord, a primary center for the transmission and processing of pain signals (39,40). Here PSD-93 plays a familiar role in targeting N-methyl-D-asparate receptors (NMDARs) to postsynaptic membranes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed similar distribution patterns for both native and ␤-neurexin-induced PSD-95 and NR2A clusters; NMDARs are present at some but not all PSD-95 clusters. It is possible that other membrane-associated guanylate kinase family members, such as PSD-93 or SAP-102 (30,31), mediate neurexin-induced and normal synaptic clustering of NMDARs.…”
Section: Discussionmentioning
confidence: 99%
“…12,19,23,69,70 Abnormal expression of these proteins could affect NMDA receptor function. Interestingly, previous studies have reported transcript expression for these PSD molecules of opposite polarity, possibly depending on the neuroanatomical structure and subject characteristics of the cohort studied.…”
Section: Discussionmentioning
confidence: 99%